Potential role of INTERLEUKIN‐17 in the pathogenesis of oral lichen planus: a systematic review with META‐analysis. (24th May 2022) - Husein‐ElAhmed, H.; Steinhoff, M.
Abstract: Oral lichen planus (OLP) is a chronic inflammatory mucocutaneous disease of unknown aetiology, which may evolve into squamous cell carcinoma. Recent advances on OLP pathogenesis suggest the presence of Th17 cells and the up‐regulation of interleukin‐17 (IL‐17) expression are crucial events. Our aim was to test the hypothesis in the literature about an important role of IL‐17 in OLP by systematically investigating the overexpression of IL‐17 in the lesional tissue and blood from OLP patients and healthy controls. A total of 22 studies comprising 658 OLP patients and 362 control subjects fulfilled inclusion criteria were subjected to meta‐analysis. The assessment of IL‐17 in the lesional tissue by quantitative real‐time polymerase chain reaction (PCR) revealed a significant elevation in the OLP group (RR:1.35 95%CI: 0.20–2.50, I 2 = 92%). There was a statistical overexpression of IL‐17 in the serum of OLP group detected by ELISA (RR:2.47 95%CI: 1.17–3.77, I 2 = 97%) and flow cytometry (RR:3.04 95%CI: 0.69–5.39, I 2 = 97%). In the erosive OLP group, the tissue IL‐17 assessed by PCR was higher than in reticular OLP patients (RR:0.78 95%CI: 0.21–1.36, I 2 = 0%). Peripheral assessment of IL‐17 by ELISA (RR:1.43 95%CI: 0.01–2.85, I 2 = 94%) and flow cytometry (RR:1.55 95%CI: 0.29–2.81, I 2 = 89%) revealed significant elevation in erosive OLP group. The dominating overexpression of IL‐17 and Th17 cells in the local inflammatory infíltrate and serum of OLP patients confirms its role, probably in the interaction between T cells and keratinocytes. Notably, the upregulation of IL‐17 is more intense in erosive than in reticular OLP suggesting a positive correlation between IL‐17 levels and disease severity. Further research is warranted to investigate the potential role of anti‐IL‐17 drugs to manage this chronic condition.